Investigation of Workers' Food and Suggestions as to Dietary - Hill, Leonard, Sir, 1866- (London : His Majesty's Stationery Office)
1917-10 1917 1910s 12 pages 9 Meals. Ingredients. Dry Weight. Protein. Fat. Carbohydrate. All four meals All kinds 146.1 137.7 442.9 Calories. Protein. Fat. Carbohydrate. Total. 599.0 1280.6 1815.9 3695.5 Sugar and milk used in tea not included in above 218.0 13. The calorie values obtained by these two analyses, 3,847 (Table III) and 3,913 (Table IV) approximate closely ; they should satisfy the requirements of factory workers, unless very heavy work is being done, and could perhaps be reduced somewhat if facilities for getting extra food are afforded to anyone who wants more. Excess food either passes into useless adipose tissue (fat) or is imperfectly utilised and impairs the digestion and efficiency. 14. The voluntary ration* recommended to the nation by the Food Controller set the fashion for substituting bread and to less extent meat by other foods. As will be shown later, the policy adopted by the Wheat Commission is to use all cereals and meals available as bread stuffs for increasing the supply of bread It is of interest, however, to consider the next table, by means of which one food can be substituted for another in equivalent values. Each of the following quantities of foods yields approximately one-tenth of the fuel value required daily by a worker doing moderately heavy work. To secure equal fuel value any one of these foods can be substituted for another in the weights given, for example, 5 oz. of meat can be substituted by 3 oz. of maize meal. In the second column are given approximately the quantities of the body-building substance (protein) present in the weights of each food given in the first column. It will be seen that 3 oz. of maize meal only yields one-third of the body-building substance which is present in 5 oz. of meat. On the other hand, 3 oz. of cheese or split peas or lentils yield not only as much fuel value as 5 oz. of meat, but as much body-building substance. It must be borne in mind that such dry foods as pea flour and meals become very bulky foods when mixed with water and cooked. Thus rice takes up five times its weight of water, and to substitute 5 oz. of meat or 3 oz. of cheese with 3 oz. of rice, no less than 15 oz. of cooked rice will have to be eaten! Bearing these facts in mind, the table can be used for guidance in substituting one food for another. As pointed out in paragraph 3, fresh vegetables, greens, salads and fruit yield certain principles most essential to health and growth, but these are not included in the table as they have in the quantities ordinarily eaten relatively little fuel value. TABLE V. SUBSTITUTION OF ONE FOOD FOR ANOTHER. One-tenth of the fuel value of the food, needed by workers doing moderately light work, is yielded very approximately by the following weights of foods:— Very approximate amounts of (protein) body-building substance in the weight of each food given in the first column. Margarine 1½ ounces. — ounce. Bacon 2 „ 1/5 „ Pork 3 „ 1/3 „ Cheese 3 „ 3/4 „ Oatmeal 3 „ 1/2 „ Sugar 3 „ — „ Split peas or beans 3 „ 3/4 „ Lentils 3 „ 3/4 „ Rice 3 „ 1/4 „ Flour 3 „ 1/3 „ Barley flour 3 „ 1/3 „ Maize meal 3 „ 1/4 „ Bread 4 „ 1/3 „ Meat (free from bone) 5 „ 3/4 „ Syrup, jam, marmalade 5 „ — „ Milk 16 fluid ounces 1/2 „ Eggs 4 in number. 1 „ Potatoes (20% allowed for waste) 17 ounces. 1/3 „ * A pennyworth of each of the following foods at the maximum retail prices approved by the Food Controller yields the number of calories shown:— Bread, 524; rolled oats, 372; potatoes, 300-400 (according to kind of potatoes); pork, 112; cheese, 111; milk, 108; jam, 100; beef, 69 ; mutton, 67. A pennyworth of margarine at 1s. 2d. a lb. gives 254, and of bacon at 1s. 7d. gives 142. 127/NU/5/5/1/1